2019
DOI: 10.1097/cm9.0000000000000539
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced anti-neutrophil cytoplasmic antibody-associated vasculitis

Abstract: Objective: In recent years, an increasing number of drugs have been proved to be associated with the induction of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). This article reviews the latest research progress on drug-induced AAV. Data sources: We conducted a comprehensive and detailed search of the PubMed database. The search terms mainly included drug-induced, ANCA, and vasculitis. Study sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 85 publications
0
33
0
Order By: Relevance
“…Although certain drugs, such as propylthiouracil, may play a role in the pathogenesis of AAV [ 9 , 10 ], the relationship between most drugs and ATIN associated with ANCA is tentative and the pathological mechanisms are unknown. Most cases of drug-induced AAV improve after withdrawal of the suspected drug, but in severe cases, steroids may be required [ 11 ]. It is, therefore, difficult to distinguish between drug-induced AAV and primary AAV based on clinical symptoms, laboratory markers, and pathological findings [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although certain drugs, such as propylthiouracil, may play a role in the pathogenesis of AAV [ 9 , 10 ], the relationship between most drugs and ATIN associated with ANCA is tentative and the pathological mechanisms are unknown. Most cases of drug-induced AAV improve after withdrawal of the suspected drug, but in severe cases, steroids may be required [ 11 ]. It is, therefore, difficult to distinguish between drug-induced AAV and primary AAV based on clinical symptoms, laboratory markers, and pathological findings [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of drug-induced AAV improve after withdrawal of the suspected drug, but in severe cases, steroids may be required [ 11 ]. It is, therefore, difficult to distinguish between drug-induced AAV and primary AAV based on clinical symptoms, laboratory markers, and pathological findings [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The culprits include anti-thyroid drugs (propylthiouracil, methimazole, carbimazole, and benzylthiouracil), tumor necrosis factor inhibitors (etanercept, infliximab, adalimumab, and golimumab) and hydralazine, rituximab, minocycline, and montelukast. Other drugs that have been shown to have a possible association with ANCA-associated vasculitis include cefotaxime, nitrofurantoin, trimethoprim-sulfamethoxazole, vancomycin, isoniazid, rifampicin, D-penicillamine, sulfasalazine, clozapine, thioridazine, allopurinol, indomethacin, atorvastatin, cocaine/levamisole, denosumab, isotretinoin, and phenytoin [ 6 ]. Because of the low incidence of drug-induced ANCA-associated vasculitis and the beneficial use of the previously mentioned drugs, there is no recommendation to preclude the use of these medications.…”
Section: Discussionmentioning
confidence: 99%
“…Druginduced antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a notable exception, in which a year or more can separate the start of the causative medication and the clinical manifestations [8]. There is a large variety of drugs associated with drug-induced ANCA-associated vasculitis which mainly include anti-thyroid drugs and tumor necrosis factor inhibitors [22]. Notably, it has been suggested that the risk of developing AAV may be related to the duration of treatment with some drugs, such as propylthiouracil [22].…”
Section: Association With Systemic Vasculitis and Other Diseasesmentioning
confidence: 99%
“…There is a large variety of drugs associated with drug-induced ANCA-associated vasculitis which mainly include anti-thyroid drugs and tumor necrosis factor inhibitors [22]. Notably, it has been suggested that the risk of developing AAV may be related to the duration of treatment with some drugs, such as propylthiouracil [22]. When the provoking agent persists, such as in hepatitis Crelated cryoglobulinemic vasculitis or rheumatoid arthritis, chronic vasculitis can be observed, with fluctuating lesions or persistent lesions of different ages.…”
Section: Association With Systemic Vasculitis and Other Diseasesmentioning
confidence: 99%